SISTEM INFORMASI PENILAIAN INDEKS KINERJA DOSEN UNIVERSITAS SAHID SURAKARTA - Andri Wahyu Septo Putra; Sri Huning Anwariningsih; suryono . (JURNAL GAUNG INFORMATIKA, 2013)
Products resulting from this study is an assessment sistem based index of faculty performance objects, which built the sistem adjusts needs assessment of facultyperformance. Features presented in information sistems, among others, provide ease of student teacher performance appraisal, assessment feedback from faculty, studentsinput data, and the ease of report generation. After testing by the method of McCall, this sistem scored 74.14% of total quality. Thus the results of such testing, the sistem isexpected to facilitate the processing of data and presenting information so that it can be applied to the University of Sahid Surakarta.